Expressed Sequence Tags (ESTs) from a Jute (Corchorus olitorius) cDNA Library - Taliaferro, J Matthew; Islam, Ahmad S; Sathasivan, Kanagasabapathi (Plant Tissue Culture and Biotechnology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Analysis of the genome of jute (Corchorus olitorius) was done by creating a new cDNA library of expressed sequence tags (ESTs) in pBluescript as the previous libraries reported earlier in this journal yielded only small DNA fragments from chloroplast and mitochondrial DNA. This report discusses results from a cDNA library constructed using poly A+ mRNA purified from 7-day old etiolated jute seedlings. Out of 700 recombinant plasmids obtained, 250 were analyzed using WU-BLAST (www.arabidopsis.org) for similar EST sequences in Arabidopsis thaliana and other higher plants. So far the analysis of the library has yielded several significant sequences, including the complete open reading frame of the 60S acidic ribosomal protein P3 and a partial cDNA of Class I chitinase. These results and future EST sequences from this library will be made available in Genbank and the sequence information will be used to clone full length DNA through PCR. Â DOI = 10.3329/ptcb.v16i2.1110 Plant Tissue Cult. & Biotech. 16(2): 95-104, 2006 (December)